Konteks Wacana dalam Novel Raja Kate Dikepung Asap Karya Abel Tasman - Agusni, Jehan Pratiwi; Fatmawati (UIR PRESS, 2021)
A good understanding of the context of the discourse will help someone in understanding the overall content of a novel. Therefore, this research is motivated by the importance of understanding the context of discourse. The problem in this research is what is the physical context, epistemic context, linguistic context, and social context in Abel Tasman's novel Raja Kate Dikepung Asap? This study aims to describe, analyze, interpret, and conclude the physical context, epistemic context, linguistic context, and social context in Abel Tasman's novel Raja Kate Dikepung Asap. The theory used to analyze the research problem is the theory of